Power and progress our thousand-year struggle over technology and prosperity - Acemoglu, Daron (New York Public Affairs, 2023)
A thousand years of history and contemporary evidence make one thing clear: progress depends on the choices we make about technology. New ways of organizing production and communication can either serve the narrow interests of an elite or become the foundation for widespread prosperity.
Includes bibliographical references (pages 475-516) and index.
Keywords: Technology--Social aspects